An overview of the traditional use, phytochemistry, and biological activity of the genus Homalanthus - Wirasisya Dyke Gita; Hohmann Judit (2023)
Homalanthus species are native to tropical Asia and the Pacific region. This genus, comprising 23 accepted species, received less scientific attention compared to other genera of the Euphorbiaceae family. Seven Homa-lanthus species, such as H. giganteus, H. macradenius, H. nutans, H. nervosus, N. novoguineensis, H. populneus, and H. populifolius, have been reported to treat various health problems in traditional medicine. Only a few Homa-lanthus species have been investigated for their biological activities, including antibacterial, anti-HIV, anti -protozoal, estrogenic, and wound-healing activities. From a phytochemical point of view ent-atisane, ent-kaur-ane, and tigliane diterpenoids, triterpenoids, coumarins, and flavonol glycosides were found to be characteristic metabolites of the genus. The most promising compound is prostratin, isolated from H. nutans, with anti-HIV activity and the ability to eradicate the HIV reservoir in infected patients by mechanism of protein kinase C (PKC) agonist. This review provides information on traditional usage, phytochemistry, and biological activity of the genus Homalanthus with the aim to delineate future research directions.
Keywords: Farmakológia és gyógyszerészet